Comparison of mechanical and ballistic performance of composite laminates produced from single‐layer and double‐layer interlocked woven structures. Issue 8 (18th December 2013) - Jabbar, Abdul; Hasan Malik, Mumtaz; Hussain, Tanveer; Zulifqar, Adeel; Tausif, Muhammad
<x xml:space="preserve">Abstract</x> Textile structures have become quite popular as reinforcement materials in composite laminates due to their high impact‐damage tolerance and energy absorption ability. The impact performance of textile composites is not only affected by the type of fiber/matrix but also by the fabric structure used as reinforcement. The aim of this study was to compare the mechanical and ballistic performance of composite laminates reinforced with single‐layer and double‐layer interlocked woven fabrics. Kevlar®−29 multifilament yarn was used for preparation of all the fabric structures and epoxy resin was used as the matrix system. The composites were produced using a hand lay‐up method, followed by compression molding. The mechanical and ballistic performance of composites reinforced with single‐layer and double‐layer interlocked woven fabrics was investigated in this study. The energy absorption and mechanical failure behavior of composites during the impact event were found to be strongly affected by the weave design of the reinforcement. The composites reinforced with double‐layer interlocked woven fabrics were found to perform better than those comprising single‐layer fabrics in terms of impact energy absorption and mechanical failure. POLYM. COMPOS., 35:1583–1591, 2014. © 2013 Society of Plastics Engineers